(untitled) (Semiárida, 2020)
Know the chemical composition of the respirable material (particles with aerodynamic diameter less than 10 microns) is relevant due to its relation with human health and the cycle of the elements. It is interesting to know the content of glyphosate in the respirable material emitted by agricultural soils, due to the extensive use of this herbicides in recent times in Argentina. The objective of this study was characterize the quality of the particulate material emitted by the different fractions of aggregate of an Haplustoll Entic under agricultural cattle management, with a history of application of agrochemicals, in the central semi - arid region of La Pampa. Three samples were taken, consisting of 3 subsamples of the first 2 cm of the soil, to which different analytical determinations were made to know the physicochemical composition of the aggregates of the soil and of the collected particulate material. The results indicated that the PM10 emitted by the aggregate fractions analyzed had similar Glyphosate concentrations ranging from 11 to 20 µg kg-1 and the concentrations of their main metabolite, aminomethyl phosphonic acid (AMPA), which fluctuated between 527.4 and 746.2 µg kg-1. No relationships were found between glyphosate content and clay, silt and organic matter contents in both, the aggregate fractions and the particulate matter collected from these fractions. Finally we concluded that the respirable material emitted by the soil and its fractions present similar contents of glyphosate and AMPA, and greater than those of the soil and fractions of aggregates.